Analisis Potensi Dan Pengembangan Kawasan Wisata Taman Eden 100 Kecamatan Lumban Julu, Kabupaten Toba Samosir, Sumatera Utara - Ricson Marpaung; Agus Purwoko; Kansih Sri Hartini (Program studi Kehutanan USU, 2015)
The development of tourism is a mainstay of the national economies. The potential of nature, culure, and the local community lives, become the foundation of its operations. Taman Eden 100 is one of the tourism object that has the potential to developed. This study aimed to analyze the potential and development of tourism object of Taman Eden 100. Identification is done by using observational methods and interviews with stakeholders. The analysis was permormed based on the criteria in Rating Analsis Object operation Guilding Nature of the Directorate General of Forest Protection and Nature Conservatoion, 2003, and SWOT analysis. The results showed that the Taman Eden 100 has decent potential to be developed on the level of 76.36%, and the feasibility of the SWOT analysis are in Quadrant I, which means to have strength that can be utilized to develop opportunities owned.Keywords: potential of tourism , development of tourism region, SWOT analysis, Taman Eden 100